The Effect of Mind Mapping Technique on Students' Writing Skills - Wahid, Jusmin HJ; Sudirman, Sari (JOLLT Journal of Languages and Language Teaching, 2023)
Writing is the process to bring concentration to the real situation, how the students focus on the ideas and elaborate in the real context. writing is not only arranging words into good sentences, but also knowing the function, meaning, and components of each word. this technique can help students develop their knowledge, think critically, and create ideas in the sentences. Students need a technique to improve their writing skills. Following this, the mind mapping technique is used to help students to improve their writing skills. The quasi-experimental research method involved two groups, namely the experimental and the control class. Both classes were given a pre-test at the beginning. Then, the experimental group was taught using mind mapping techniques while the control group was taught without mind mapping techniques. Then, this research gave the instrument in the last session of this study, both groups were given a post-test. Then for data collection, researchers used a written test and data analysis using a t-test. It proves that there was a significant score on the t-test and the mean score of the experimental class and control class. In the experimental class score is 3.0 and the mean is 28.25. While in the control class, the t-test score is 3.0 and the mean score is 25.00. It proves that mind mapping techniques are an effective way to help students to overcome problems such as nervousness and not being confident to improve their writing skills, it also helps the students to organize systematic ideas and make them easy meaning to understand.